Frequent activity on Vulcano (Italy) spanning the last 80 ky: new insights from the chemo-stratigraphy of the Brown Tuffs - Meschiari, S; Albert, PG; Lucchi, F; Sulpizio, R; Smith Johnson, VC; Kearney, R; Tranne, CA (Elsevier, 2020)
The Brown Tuffs (BT) are widespread reddish-brown to grey, ash-rich pyroclastic deposits recognized in the stratigraphic sequences of the Aeolian Islands and Capo Millazzo peninsula (Sicily) that span the last 80 ky. They have very homogeneous lithological, textural and sedimentological features which make it difficult to reliably correlate units on the islands to proximal units in the source areas. Here we carefully re-interpret the stratigraphic profiles of the BT on Vulcano and Lipari where the deposits are thickest and present the most complete succession. The investigation is based on a large dataset of major and minor element geochemistry of juvenile glass components for the majority of the recognized BT depositional units, whilst also providing new radiocarbon ages. The distinctive chemical groupings observed within the glass analyses, both temporally and spatially, allow us to fingerprint the three main stratigraphically defined macro-units in which the BT succession can be sub-divided using prominent tephra marker beds, the Ischia Tephra (Monte Epomeo Green Tuff; 56 ky) and Monte Guardia pyroclastics from Lipari (herein radiocarbon dated to 27–26 ky). The Lower (80–56 ky; LBT), Intermediate (56–27 ky; IBT) and Upper BT (here dated at 24–6 ky; UBT) macro-units display K-series volcanic glasses ranging from basaltic trachy-andesites, through trachy-andesites, to more evolved trachytes, all consistent with an origin on Vulcano. The UBT are clearly distinguished from the lower macro units by their higher-SiO2 trachy-andesite to trachytic glasses, which extend to noticeably lower TiO2, CaO and MgO contents. These features make it possible to re-define the geochemical-evolutionary boundary between IBT and UBT as corresponding to the 24 ky Spiaggia Lunga scoria bed on Vulcano, which is stratigraphically higher (and younger) than the previous boundary marker (Monte Guardia). The glass compositions of the LBT, IBT and UBT are used to: (1) assess links to known proximal eruption units outcropping on Vulcano; (2) validate medial-distal BT occurrences across the Aeolian archipelago (Salina, Filicudi and Panarea) and on Capo Millazzo; (3) confirm that the BT are responsible for distal volcanic ash layers preserved in Central Mediterranean marine sedimentary archives. Interestingly, the glass compositions of the UBT are very similar to those of the Punte Nere unit, the earliest pyroclastic products erupted from the currently active La Fossa cone on Vulcano, indicating the corresponding magmatic system has likely erupted similar melts and products over the last 24 ky and thus extending its life cycle. Such information is crucial for evaluating the long-term eruption scenarios underpinning hazard assessment of the La Fossa caldera magmatic system.